DINAMIKA STUDI ISLAM DI BARAT - Rusydi, M (Jurnal Studia Insania, 2016)
The following writing shows the historicity of Islamic studies in the West. It is important to reflect, at least as a comparison for our Islamic studies in Indonesia. Initially, Islamic studies in the West were looked unfairly. Islam was considered a fragment of Jews and Christian tradition. Thus, Islamic studies were positioned as a subunit of Christian studies. At this condition, Islamic studies tended to be colonized by West scholars? ideology. However, in 1980, Islamic studies began to be looked fairly in the West. Funded by National Endowment for the Humanities, University of Arizona for the first time held an international symposium on Islam and Religious Studies. In this symposium, Islam was considered equally with Christian. Therefore, the research on it was not only about Islam as religion but also as civilization. It was indicated by various approaches to Islam such as philology, social and humanities approaches. Today, Islamic studies develop intensively with the contemporary approaches called post-orientalism which is based on post-colonialism, post-structuralism, multiculturalism, and critical theory.